Sex‐specific variation in facial masculinity/femininity associated with autistic traits in the general population. (5th December 2019) - Tan, Diana Weiting; Maybery, Murray T.; Ewing, Louise; Tay, Jia‐Xin; Eastwood, Peter R.; Whitehouse, Andrew J.O.
Abstract : Reports linking prenatal testosterone exposure to autistic traits and to a masculinized face structure have motivated research investigating whether autism is associated with facial masculinization. This association has been reported with greater consistency for females than for males, in studies comparing groups with high and low levels of autistic traits. In the present study, we conducted two experiments to examine facial masculinity/femininity in 151 neurotypical adults selected for either low, mid‐range, or high levels of autistic traits. In the first experiment, their three‐dimensional facial photographs were subjectively rated by 41 raters for masculinity/femininity and were objectively analysed. In the second experiment, we generated 6‐face composite images, which were rated by another 36 raters. Across both experiments, findings were consistent for ratings of photographs and composite images. For females, a linear relationship was observed where femininity ratings decreased as a function of higher levels of autistic traits. For males, we found a U‐shaped function where males with mid‐range levels of traits were rated lowest on masculinity. Objective facial analyses revealed that higher levels of autistic traits were associated with less feminine facial structures in females and less masculine structures in males. These results suggest sex‐specific relationships between autistic traits and facial masculinity/femininity.